KONTROL NEGARA ATAS TUBUH PEREMPUAN: PRO KONTRA RUU ANTIPORNOGRAFI DAN PORNOAKSI PADA MASYARAKAT KOTA SEMARANG - Lestari, Puji (Forum Ilmu Sosial, 2009)
Indonesian state, with the culture of patriarchy inherent in community life, always put women in positions that are diffcult and cornered. With his power, often state that does not make policy gender sensitive. Including today, where the bill becomes law product APP disturbing for some people. This study raised the issue about How Semarang citizen opinion about the Pornoaction and pornography? How Semarang citizen opinion about the content of RUU APP and position of women in society? What factors are inhibiting the implementation of the bill into law APP? The purpose of this study was to determine public opinion of the Semarang citizen about Pornoaction and pornography, knowing the public opinion of the Semarang citizen about the content of bill APP and the position of women in society and what factors are inhibiting the implementation of the bill into law APP. The results of this study is the emergence of the Draft Law on Anti-pornography and Pornoaction, provides an illustration of the growing infuence of the state to the women’s bodies. This led to a public anxiety about the position of women is increasingly cornered. Pros and cons of the contents of the Bill of APP caused by multiple interpretations of the contents of the articles RUU APP. In addition, also due to the assessment and perspectives of different communities about the content of this RUU APP. Community pro Semarang RUU APP argues that the existence of RUU APP can protect the nation from moral destruction, especially for the younger generation. While that does not agree with the existence of this bill due to cultural differences, as well as the position of women that are cornered.Keywords: Pornography, Pornoaction